An Anthropology of Ethics - Faubion, James D. 1957- (New departures in anthropology., 2011)
Through an ambitious and critical revision of Michel Foucault's investigation of ethics, James Faubion develops an original program of empirical inquiry into the ethical domain. From an anthropological perspective, Faubion argues that Foucault's specification of the analytical parameters of this domain is the most productive point of departure in conceptualizing its distinctive features. He further argues that Foucault's framework is in need of substantial revision to be of genuinely anthropological scope. In making this revision, Faubion illustrates his program with two extended case studies: one of a Portuguese marquis and the other of a dual subject made up of the author and a millenarian prophetess. The result is a conceptual apparatus that is able to accommodate ethical pluralism and yield an account of the limits of ethical variation, providing a novel resolution of the problem of relativism that has haunted anthropological inquiry into ethics since its inception.